Research in personnel and human resources management. Vol. 37 - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben, Jonathon R. B. (Bingley, U.K. : Emerald Publishing Limited, 2019)
Volume 37 of Research in Personnel and Human Resources Management contains six original scholarly monographs written by thought leaders in the field of human resources management. This volume focuses on human resources branding, innovation and creativity in human resources management, high involvement work systems, work home boundary permeability, the emerging concept of grit in human resources management, and data visualization issues in human resources management.
Prelims -- Chapter 1: High-involvement work processes and systems: a review of theory, distribution, outcomes, and tensions -- Chapter 2: The roles of grit in human resources theory and research -- Chapter 3: Data visualizations and human resource management: the state of science and practice -- Chapter 4: Organizational influences on workhome boundary permeability: a multidimensional perspective -- Chapter 5: Third party employment branding: what are its signaling dimensions, mechanisms, and sources? -- Chapter 6: Reviewing creativity and innovation research through the strategic HRM lens -- About the authors.
Print version record
Keywords: Personnel management; Business & Economics -- Human Resources & Personnel Management; Personnel & human resources management